PKM Pengembangan Usaha Olahan Leumeung dengan Variasi Rasa Serbuk Kacang Kedelai di Desa Cijakan Bojong Pandeglang - Wiguna, Wahyu; Rahma, Destiana; Damayanti, Winda; Hafifah, Hafifah (Batara Wisnu : Indonesian Journal of Community Services, 2022)
Food security is one of the determining factors for the welfare of the community, especially in rural areas. Efforts to achieve this condition require cooperation between various elements, one of which is the role of universities through community service activities. The PKm Group and the KKM 63 Group of Bina Bangsa University as change agents try to develop leumeng products by providing a variety of unique and delicious flavors so that they are easily recognized by the people in Indonesia. The method used is a method of cutting down the making of flavor variations for leumeng products in Cijakan Village.m The result is achieved by creating a variety of flavors made from soybean ingredients that are processed into soybean powder to be eaten together with Leumeung. The variety of flavors in the leumeung of Cijakan village is expected to be one of the people's interest in buying Leumeung from cijakan village so that it can increase MSMEs in the area to continue to work and be able to produce leumeng products that are global